Research of the effects of autologous cancellous bone graft and hyaluronic acid on the healing of bone defects experimentally induced in rabbits - Sagliyan, Aydin; Han, Mehmet Cengiz; Karabulut, Enis; Ozkaraca, Mustafa (Tubitak Scientific & Technological Research Council Turkey, 2016)
The present study investigated the effect of autograft and hyaluronic acid (HA) in terms of clinical, radiological, and histopathological aspects on the healing of experimentally induced bone defects. The animals (n = 42) were assorted into 3 groups. After general anesthesia, a 3-mm standard defect was formed from the tibia of the experimental animals. The defects in Group I (n = 14) were left blank. Cancellous grafts in the proximal tibia were collected using a small curette to fill the defects in Group II (n = 14). The defects in Group III (n = 14) were filled by mixing with HA and cancellous grafts taken from the same region of the tibia. To determine the course of healing in the 3 groups in terms of clinical, radiological, and histopathological aspects, 7 rabbits from each group were chosen randomly on days 35 and 70 postsurgery and euthanized under anesthesia. Consequently, higher scores in terms of bone healing criteria were obtained in Group II, in which the graft was applied, compared with Group I. In Group III, in which the graft material was combined with HA, more healing was achieved compared with both Group I and Group II.
Keywords: Bone defect; hyaluronic acid; autograft; rabbits